Fosthiazate inhibits root-knot disease and alters rhizosphere microbiome of Cucumis melo var. saccharinus - Wang, Huifang; Yan, Wanrong; Luo, Jiguang; Zeng, Xiangping; Zhao, Zhixiang; Dou, Xiaoli; Fu, Meiying (Frontiers in Microbiology, 2023)
Root-knot nematodes especially Meloidogyne spp. are considered as most destructive obligate parasites that substantially reduce crop yield and quality. Fosthiazate is an efficient organothiophosphate chemical with nematicidal activity against Meloidogyne spp. The present study aimed to analyze the efficacy of fosthiazate against root-knot disease in Cucumis melo var. saccharinus and its potential effects on rhizosphere microbiome and metabolites. The fosthiazate (40%) was applied two times by spraying on the day of transplanting and during the pollination period (after 31 days). Samples from treatment (fosthiazate 40%: MF) and control groups (untreated plants; MCK) were analysed through metagenomic and metabolomic profiling of rhizospheres. Results revealed that root-knot index of the MF group (9.26 ± 1.28) was significantly (p < 0.05) lower than the MCK group (22.06 ± 0.71) with a control effect of 57.85% after 31 days of the first spray, whereas fosthiazate efficacy reduced to 31.87% after 38 days of second application with significantly (p < 0.05) different root-knot index values (MF: 56 ± 1.43 and; MCK: 82.26 ± 3.87). However, Cucumis melo var. saccharinus fruit yield in both groups (MCK: 21.1 ± 0.9 and MF: 21.53 ± 0.85) showed no differences (p > 0.05). Metagenomic profiling revealed Proteobacteria, Acidobacteriota, and Firmicutes as predominant phyla and Bacillus, Sphingomonas, and Acidibacter as predominant genera in rhizosphere soil samples of both MF and MCK groups. Higher diversity of bacterial communities was observed in treatment group as compared to the control as revealed by the significantly different alpha diversity (Simpson and Shannon indices) and beta diversity values (p < 0.05). Metabolomic profiling of rhizospheric soil revealed a total of six differential metabolites (p < 0.05), four of them (Sucrose, Hexaonic acid 1, (Z)-9-Octadecenamide 1, and Hexadecanamide) were up-regulated in MF group, whereas two of them (2,3,4-Trihydroxy-3-(Hydroxymethyl) Butanol and Sulfurous acid, 2, ethylhexylundecyl ester) were down-regulated in CK group. Our study concluded that fosthiazate exhibits a better control over the rook-knot disease in the short term through promoting bacterial diversity and metabolites enrichment.